120Sn(p,α)117In and 121Sb(p,α) 118Sn Reactions: Identification of the 117In and 118Sn Homologous States - Jaskola M.; Wirth H.-F.; Faestermann T.; Hertenberger R.; Zetta L.; Guazzoni P. (EPJ Web of Conferences, 2010)
To investigate the spectator role of the d5/2 unpaired proton outside the Z=50 closed shell, the 120Sn(p,α) 117In and 121Sb(p,α)118 Sn reactions have been measured in high resolution experiments, performed with the 23 MeV proton beam of the Munich MP Tandem, using the Stern-Gerlach type polarized hydrogen ion source and the Q3D magnetic spectrograph.